Blown film extrusion - Cantor, Kirk (Hanser Publishers, Hanser Publications, 2019)
"From hardware and materials through processing and properties, a broad coverage of blown film extrusion is presented. A primary objective of this book is to ensure a useful balance of theory and practice. The reader will find the answers to why they encounter certain effects in the blown film process so that they are better able to troubleshoot and improve their operations. At the same time, current practices and equipment are emphasized to keep readers up-to-date with the most productive and efficient technology. The companion computer-based learning tool, The Blown Film Extrusion Simulator, is provided to enhance the reader's understanding. This software was developed specifically to teach blown film extrusion equipment operation and processing principles, and is available for download. Throughout this book, exercises using the simulator are described to complement the methods and principles explained. New in this third edition is a chapter on polymer rheology, with an overview of the rheology of polymer melts and its effect on extruding blown film. Additionally, improvements and corrections have been made throughout the book. Contents: Materials for Blown Film Polymer Rheology Extrusion Overview Hardware for Blown Film Processing Coextrusion Film Properties Troubleshooting"--